2018
DOI: 10.21037/atm.2018.08.21
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence and seasonal variation of hypovitaminosis D in patients scheduled for lower extremity total joint arthroplasty

Abstract: Background: High rates of vitamin D insufficiency and deficiency have been demonstrated in various patient populations, including patients undergoing total joint arthroplasties (TJA). However, the risk factors associated with this condition and its seasonal variation is still to be determined in patients scheduled for elective TJA. Methods: We retrospectively identified 226 (116 hips, 120 knees) patients who underwent primary TJA, and had a vitamin D measurement, at a single institution (latitude, 41° 30' N) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 34 publications
0
26
0
1
Order By: Relevance
“…4,24,32 Furthermore, vitamin D receptors have been found on myocytes, which may act as a modulator of cell growth, neuromuscular function, and immunomodulation. 60 After anterior cruciate ligament reconstruction (ACLR), muscle (quadriceps) weakness is an immediate and persistent impairment that can predispose patients to developing degenerative joint disease and requiring subsequent surgeries later in life. To explore the potential clinical therapeutic benefit of vitamin D to combat these changes in the postoperative setting, Barker et al 8 measured changes in peak isometric forces in the injured limb of patients undergoing ACLR in vitamin D-insufficient (<30 ng/mL) and sufficient (≥30 ng/mL) patients.…”
Section: Hypovitaminosis Dmentioning
confidence: 99%
See 2 more Smart Citations
“…4,24,32 Furthermore, vitamin D receptors have been found on myocytes, which may act as a modulator of cell growth, neuromuscular function, and immunomodulation. 60 After anterior cruciate ligament reconstruction (ACLR), muscle (quadriceps) weakness is an immediate and persistent impairment that can predispose patients to developing degenerative joint disease and requiring subsequent surgeries later in life. To explore the potential clinical therapeutic benefit of vitamin D to combat these changes in the postoperative setting, Barker et al 8 measured changes in peak isometric forces in the injured limb of patients undergoing ACLR in vitamin D-insufficient (<30 ng/mL) and sufficient (≥30 ng/mL) patients.…”
Section: Hypovitaminosis Dmentioning
confidence: 99%
“…73 Vitamin D deficiency and insufficiency, defined as <20 ng/mL and <30 to 32 ng/mL, respectively, are highly prevalent in patients undergoing orthopaedic procedures. 11,60 Second only to trauma patients, Bogunovic et al 11 demonstrated a 52.3% rate of vitamin D insufficiency in orthopaedic sports medicine patients.…”
Section: Hypovitaminosis Dmentioning
confidence: 99%
See 1 more Smart Citation
“…73 Most research, however, demonstrates little evidence to support hypovitaminosis D as a risk factor linked to reduced postoperative functional recovery or increased risk of PJIs. 74,75 Some orthopedists nevertheless recommend screening and treating hypovitaminosis D prior to undergoing orthopaedic surgery. 74 When recommended, a standard vitamin D regimen consists of 50,000 units of vitamin D 3 weekly for 6 to 8 weeks to increase low levels to an optimal level of 30 to 60 ng/mL.…”
Section: Vitamin D Deficiency/insufficiencymentioning
confidence: 99%
“…13,15 In recent years, several studies have demonstrated that vitamin D deficiency is highly prevalent in orthopedic patients. 20,23,30 Moreover, we and others have shown that vitamin D deficiency also affects patients with foot and ankle disorders. 1,16,32,33 Further, it has been suggested that hypovitaminosis D is related to the onset of OCD.…”
mentioning
confidence: 99%